Kajian Indeks Pengaruh Komitmen Organisasi Dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan - Muhammad Haris Syafitri; Edy Mahfuz; Dewi Ariefahnoor; Ridha Septina Arini (Pusat Riset dan Inovasi Nasional, 2026)
This is one of the elements that has been proven to have a significant impact on performance and commitment to the organization. The organization's commitment can be maintained as long as the organization maintains loyalty and is emotionally connected to the organization they work with. Organizational commitment does not only play a role in forming loyalty, but also becomes the foundation for the formation of optimal performance. Employees who have an attachment to their organization tend to exhibit positive work behaviors, including a willingness to work extra hard, complete tasks on time, and serve the company well. They are not only motivated by working for the good of their organization, but are also driven by a desire to see their organization grow and develop. In addition to organizational commitment, other factors also influence the performance of the organization's activities and behavior which is known as Organizational Civil Service Behavior (OCB). OCB includes positive behavior such as assisting with work plans, complying with the tasks to be achieved, taking initiative in completing the tasks achieved, and being willing to achieve the tasks that are achieved. Based on the results of the research on the influence of the Organizational Commitment on the Organization of the Organization and the Behavior of the performance to employees, obtained a total of 9588,650 data f table 3.15 significant data up to 0.000 < 0.05 so that H0 is rejected and O is accepted. This shows that the organization has a continuous positive influence and significant influence on the organization's commitment to the organization's performance..